Inhibition of Mycoplasma pneumoniae growth by FDA-approved anticancer and antiviral nucleoside and nucleobase analogs - Sun, Ren (BioMed Central, 2013)
BACKGROUND: Mycoplasma pneumoniae (Mpn) is a human pathogen that causes acute and chronic respiratory diseases and has been linked to many extrapulmonary diseases. Due to the lack of cell wall, Mpn is resistant to antibiotics targeting cell wall synthesis such as penicillin. During the last 10 years macrolide-resistant Mpn strains have been frequently reported in Asian countries and have been spreading to Europe and the United States. Therefore, new antibiotics are needed. In this study, 30 FDA-approved anticancer or antiviral drugs were screened for inhibitory effects on Mpn growth and selected analogs were further characterized by inhibition of target enzymes and metabolism of radiolabeled substrates. RESULTS: Sixteen drugs showed varying inhibitory effects and seven showed strong inhibition of Mpn growth. The anticancer drug 6-thioguanine had a MIC (minimum inhibitory concentration required to cause 90% of growth inhibition) value of 0.20 μg ml(-1), whereas trifluorothymidine, gemcitabine and dipyridamole had MIC values of approximately 2 μg ml(-1). In wild type Mpn culture the presence of 6-thioguanine and dipyridamole strongly inhibited the uptake and metabolism of hypoxanthine and guanine while gemcitabine inhibited the uptake and metabolism of all nucleobases and thymidine. Trifluorothymidine and 5-fluorodeoxyuridine, however, stimulated the uptake and incorporation of radiolabeled thymidine and this stimulation was due to induction of thymidine kinase activity. Furthermore, Mpn hypoxanthine guanine phosphoribosyl transferase (HPRT) was cloned, expressed, and characterized. The 6-thioguanine, but not other purine analogs, strongly inhibited HPRT, which may in part explain the observed growth inhibition. Trifluorothymidine and 5-fluorodeoxyuridine were shown to be good substrates and inhibitors for thymidine kinase from human and Mycoplasma sources. CONCLUSION: We have shown that several anticancer and antiviral nucleoside and nucleobase analogs are potent inhibitors of Mpn growth and that the mechanism of inhibition are most likely due to inhibition of enzymes in the nucleotide biosynthesis pathway and nucleoside transporter. Our results suggest that enzymes in Mycoplasma nucleotide biosynthesis are potential targets for future design of antibiotics against Mycoplasma infection.